El argumento ontológico y la muerte de la metafísica: dos visiones complementarias – Kant y Hegel = The ontological argument and the end of metaphysics: two complementary approaches – Kant and Hegel - Ferreiro, Héctor (Veritas)
The core of Kant’s criticism of the ontological argument is the thesis that existence is not a real predicate capable of being added to the concept of an object. The concept of the most perfect or the most real being is a subjective content that is as such completely determined, that is to say, that already has all the determinations that define that concept as such. Therefore, to know if that object also exists in the real world is indispensable that the subject has an intuition of it. The absence of such intuition is, according to Kant, an insuperable obstacle for the different attempts to prove the existence of God. Although Hegel agrees in principle with Kant´s claim that existence must not be conceived as a real predicate, he considers, however, that to understand it as the position of the already exhaustively determined concept of the object does not imply a true overcoming of the particular notion of existence that is at the base of the ontological argument. In this article I defend the claim that Hegel´s counter-criticism of Kant´s criticism of the ontological argument is actually a radicalization of Kant´s general critique of metaphysics